Kenyamanan Spiritual Muzaki dalam Pembayaran Zakat secara Tradisional di Kalimantan Selatan - Maulida, Sri; Amruzi, Fahmi Al; Hakim, Budi Rahmat; Beik, Irfan Syauqi (Universitas Gadjah Mada, 2025)
During the Covid-19 pandemic, zakat played a crucial role in mitigating the community’s economicrisks. Although technological developments have encouraged the emergence of digital zakat paymentplatforms, their adoption in South Kalimantan has been relatively slow. Many zakat payers (muzaki) continue to prefer traditional methods of zakat payment. This study aims to understand the reasons behind this preference by examining muzaki’s perceptions, subjective norms,and attitudes, as well as their relation to the spiritual comfort they experience. Using a qualitative approach,data were collected through in-depth interviews with academics, zakat payers, and staff from Zakat Management Organizations (BAZNAS and LAZNAS) in South Kalimantan. The findings reveal that muzaki’s perceptions of traditional zakat payment are driven by several key factors, including proximity to zakatreceiving institutions, deeply rooted habits, ease of implementation, and negative perceptions of digital zakat methods. Muzaki’s subjective norms regarding zakatare shaped by various sources of knowledge, such as digital media, BAZNAS services, government initiatives,print media, banking institutions, self-initiative, family,religious scholars, digital literacy, and peers. Muzaki’s attitudes in the re-actualization of zakat managementare reflected in efforts to explain zakat payment methods at BAZNAS, provide information about zakat institutions,encourage others to pay zakat, and describe zakat distribution and utilization programs. In addition, the study finds that factors influencing muzaki’s decision to pay zakat directly include the perceived importance of akad (contract) in zakat payment, satisfaction, the use of bank accounts, the lack of legal endorsementand socialization from the Indonesian Ulema Council (MUI), as well as limited communication about zakat digitalization, which leads some muzaki to reject digital zakat payments. Theoretically, these findings reinforce the Theory of Planned Behavior, the concept of maslahah in Islamic economics, and the Spiritual Well-being Theory in explaining the interconnectedness of religious values, culture, and spiritual comfort with muzaki behavior. Practically, the results provide insights for zakat institutions to design digitalization strategies that are sensitive to spiritual and local cultural values,ensuring that technological innovation aligns with the preservation of meaningful religious practices.